Inovasi Pelajar dan Penggunaan Sistem Teknologi Pendidikan Baru Setelah Pandemi COVID-19 - Uswatiyah, Wiwi; Ernawati, Ernawati; Aminah, Siti; Setiawati, Yanti Hasbian (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This study aims to identify the factors that influence the use of a new online learning system by students in tertiary institutions, especially in Indonesia. The results of the research show that students' innovativeness has a positive influence on their willingness to use the system. In addition, learning interactions in a subject can increase student learning satisfaction. Innovation can also link between learning satisfaction, intention to use the system, and the expected impact of the system. In the context of the COVID-19 pandemic and social distancing policies, the new online learning system has become a necessary educational service. Although many universities have shifted back to in-person courses, online learning systems can be a meaningful complement to traditional learning methods. This study emphasizes the importance of students' innovativeness in adopting a new online learning system. Good interaction between instructors and students is also important to increase learning satisfaction. The findings of this study indicate that instructors and universities need to provide new opportunities to increase students' willingness and motivation to take online courses and interact in learning. However, keep in mind that this study has some limitations. The data used in this study is limited to students majoring in management and other fields in Indonesia. Furthermore, future research can broaden the scope by involving data from universities in other countries. Key words: Learner Innovation, Mixed Learning, Learning Interaction Education, Management Educational Innovation